Round-Robin Algorithm in Load Balancing for National Data Centers - Sudiatmika, I Kadek Wahyu; Indrawan, Gede; Sariyasa, Sariyasa (Knowledge Engineering and Data Science, 2023)
The Provincial Government of Bali assumes a crucial role in administering various public service applications to meet the requirements of its community, traditional villages, and regional apparatus. Nevertheless, the escalating magnitude of traffic and uneven distribution of requests have resulted in substantial server burdens, which may jeopardize the operation of applications and heighten the likelihood of downtime. Ensuring efficient load distribution is of utmost importance in tackling these difficulties, and the Round Robin algorithm is often utilized for this purpose. However, the current body of research has not extensively examined the distinct circumstances surrounding on-premise servers in the Bali Provincial Government. The primary objective of this study is to address the significant gap in knowledge by conducting a comprehensive evaluation of the Round Robin algorithm's effectiveness in load-balancing on-premise servers inside the Bali Provincial Government. The primary objective of our study is to assess the appropriateness of the algorithm within the given context, with the ultimate goal of providing practical and implementable suggestions. The observations above can optimize system efficiency and minimize periods of inactivity, thereby enhancing the provision of vital public services across Bali. This study provides essential insights for enhancing server infrastructure and load-balancing strategies through empirical evaluation and comprehensive analysis. Its findings are valuable for the Bali Provincial Government and serve as a reference for other organizations facing challenges managing server loads. This study signifies a notable advancement in establishing reliable and practical public service applications within Bali.